Developmental and cancer-associated plasticity of DNA replication preferentially targets GC-poor, lowly expressed and late-replicating regions. Issue 19 (5th September 2018) - Wu, Xia; Kabalane, Hadi; Kahli, Malik; Petryk, Nataliya; Laperrousaz, Bastien; Jaszczyszyn, Yan; Drillon, Guenola; Nicolini, Frank-Emmanuel; Perot, Gaëlle; Robert, Aude; Fund, Cédric; Chibon, Frédéric; et al.
Abstract: The spatiotemporal program of metazoan DNA replication is regulated during development and altered in cancers. We have generated novel OK-seq, Repli-seq and RNA-seq data to compare the DNA replication and gene expression programs of twelve cancer and non-cancer human cell types. Changes in replication fork directionality (RFD) determined by OK-seq are widespread but more frequent within GC-poor isochores and largely disconnected from transcription changes. Cancer cell RFD profiles cluster with non-cancer cells of similar developmental origin but not with different cancer types. Importantly, recurrent RFD changes are detected in specific tumour progression pathways. Using a model for establishment and early progression of chronic myeloid leukemia (CML), we identify 1027 replication initiation zones (IZs) that progressively change efficiency during long-term expression of the BCR-ABL1 oncogene, being twice more often downregulated than upregulated. Prolonged expression of BCR-ABL1 results in targeting of new IZs and accentuation of previous efficiency changes. Targeted IZs are predominantly located in GC-poor, late replicating gene deserts and frequently silenced in late CML. Prolonged expression of BCR-ABL1 results in massive deletion of GC-poor, late replicating DNA sequences enriched in origin silencing events. We conclude that BCR-ABL1 expression progressively affects replication and stability of GC-poor, late-replicating regions during CML progression.